A Conceptual Framework for Developing an Arabic Qawāʾid Curriculum Based on Cognitive Grammar - Aufa Rahma; Firman Alamsyah; Nursyahidatul Urwati; Muhajir Muhajir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Arabic qawāʾid learning in formal education remains predominantly influenced by rule-based approaches that emphasize memorization and formal grammatical accuracy rather than meaningful language use. This condition often separates grammatical structures from communicative contexts and learners’ cognitive processes, resulting in difficulties in applying grammatical knowledge in authentic communication. This study addresses the question of how Cognitive Grammar can provide a conceptual foundation for developing a more contextual and meaning-oriented Arabic qawāʾid curriculum. Using a literature study method with a descriptive-analytical approach, this study analyzes relevant works on Cognitive Grammar, Arabic grammar instruction, and curriculum development collected from academic books, journal articles, and related scholarly publications. The analysis focuses on identifying conceptual principles, curriculum components, and sequencing patterns relevant to Cognitive Grammar–based qawāʾid curriculum development. The findings show that a Cognitive Grammar–based curriculum positions grammar as a meaningful symbolic system grounded in cognition and usage-based language experience. The proposed framework integrates learning objectives, instructional materials, learning processes, evaluation, and sequencing within a coherent meaning-based system. In addition, qawāʾid content sequencing is organized based on meaning salience, usage frequency, prototypicality, and conceptual accessibility rather than formal grammatical complexity. The conceptual contribution of this study lies in offering an integrative framework that connects Cognitive Grammar principles with Arabic qawāʾid curriculum design in a systematic and pedagogically oriented manner. This study concludes that Cognitive Grammar provides a meaningful conceptual foundation for developing a more contextual, cognitively aligned, and communicative Arabic qawāʾid curriculum.